The prognostic value of Clinical Frailty Scale in COVID-19 pneumonia across different pandemic phases: a comparison between the first and the fourth wave - Siniscalchi, Carmine; Ticinesi, Andrea; Guerra, Angela; Parise, Alberto; Cerundolo, Nicoletta; Prati, Beatrice; Simoni, Riccardo; Porro, Emanuela; Meschi, Tiziana (Frontiers in Medicine, 2025)
IntroductionThe COVID-19 pandemic has placed unprecedented strain on health-care systems. Frailty is being used in clinical decision making for patients with COVID-19, yet the prevalence and effect of frailty in people with COVID-19 may be influenced by the local characteristics of each pandemic wave. We aimed to establish the prevalence of frailty in older patients with COVID-19 who were admitted to hospital and investigate its association with mortality comparing non-vaccinated patients of the first wave versus vaccinated patients in the fourth wave.Materials and methodsThis was an observational study conducted at one single hospital center in Italy. All older adults (≥70 years) admitted with confirmed COVID-19 (positive molecular testing) were included. Data of 658 patients (493 non-vaccinated COVID-19 patients admitted during the first wave and 165 patients vaccinated against COVID-19 during the fourth wave), were collected from clinical records including symptom type, extension of lung abnormalities on chest computed tomography (CT), laboratory parameters. Frailty was assessed by Clinical Frailty Scale (CFS) and patients were grouped according to their score (≤4: fit or pre-frail; 5–6 = initial signs of frailty but with some degree of independence; >7 = severe or very severe frailty). The primary outcome was in-hospital mortality.ResultsIn comparison with vaccinated patients from the fourth wave, unvaccinated patients from the first wave had reduced prevalence of heart disease (35% vs. 56%), renal failure (9% vs. 15%), but higher prevalence of fever at time of diagnosis (84% vs. 59%), malignancy (16% vs. 6%), higher computed tomography (CT) severity visual score, higher CRP (C-reactive protein) serum levels (median value 105 mg/L vs. 75 mg/L), but lower burden of frailty. In a stepwise multivariable logistic regression model, unvaccinated patients from the first wave had a higher risk of death regardless of CFS [Odds Ratio (OR) 2.241, 95% confidence interval (CI) 1.492–3.336, p < = 0.001], while in the fourth wave, CFS was significantly associated with hospital mortality.ConclusionOur study suggests that in non-vaccinated older patients from the first pandemic wave CFS was unable to stratify the risk of death.